Update on Perineuronal Net Staining With Wisteria floribunda Agglutinin (WFA) - Härtig, Wolfgang; Meinicke, Anton; Michalski, Dominik; Schob, Stefan; Jäger, Carsten (Frontiers in Integrative Neuroscience, 2022)
As chemically specialized forms of the extracellular matrix in the central nervous system, polyanionic perineuronal nets (PNs) contain diverse constituents, including chondroitin sulfate proteoglycans (CSPGs), hyaluronic acid, and tenascins. They are detectable by various histological approaches such as colloidal iron binding and immunohistochemical staining to reveal, for instance, the CSPGs aggrecan, neurocan, phosphacan, and versican. Moreover, biotin, peroxidase, or fluorescein conjugates of the lectins Vicia villosa agglutinin and soybean agglutinin enable the visualization of PNs. At present, the N-acetylgalactosamine-binding Wisteria floribunda agglutinin (WFA) is the most widely applied marker for PNs. Therefore, this article is largely focused on methodological aspects of WFA staining. Notably, fluorescent WFA labeling allows, after its conversion into electron-dense adducts, electron microscopic analyses. Furthermore, the usefulness of WFA conjugates for the oftentimes neglected in vivo and in vitro labeling of PNs is emphasized. Subsequently, we discuss impaired WFA-staining sites after long-lasting experiments in vitro, especially in autoptic brain samples with long postmortem delay and partial enzymatic degradation, while immunolabeling of aggrecan and CSPG link proteins under such conditions has proven more robust. In some hippocampal regions from perfusion-fixed mice, more PNs are aggrecan immunoreactive than WFA positive, whereas the retrosplenial cortex displays many WFA-binding PNs devoid of visible aggrecan immunoreactivity. Additional multiple fluorescence labeling exemplarily revealed in ischemic tissue diminished staining of WFA-binding sites and aquaporin 4 and concomitantly upregulated immunolabeling of neurofilament, light chains, and collagen IV. Finally, we briefly discuss possible future staining approaches based on nanobodies to facilitate novel technologies revealing details of net morphology.